PARTISIPASI PEMUDA DALAM PENGEMBANGAN KAWASAN EKOWISATA DAN IMPLIKASINYA TERHADAP KETAHANAN MASYARAKAT DESA (Studi di Kawasan Ekowisata Gunung Api Purba Nglanggeran, Desa Nglanggeran, Kecamatan Patuk, Kabupaten Gunung Kidul, Provinsi Daerah Istimewa Yogyakarta) - , Idah Rosida ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study discusses public participations in developing ecotourism area and its implications for the villagers resilience. This research was conducted in the ecotourism area of Ancient Volcano Nglanggeran which is administratively located in Nglanggeran village, Patuk, Gunung Kidul, Yogyakarta Special Region. The purposes of this study are (1) to determine the form of youth participations in developing ecotourism area of Ancient Volcano Nglanggeran, (2) to analyze the constraints faced by the youth in developing ecotourism area of Ancient Volcano Nglanggeran, (3) to identify youth efforts in developing ecotourism area of Ancient Volcano Nglanggeran and its implications for the villagers resilience This study is a descriptive qualitative . exposure. The approach used in this study is a study of the problems in society The results shows that youths in the Nglanggeran village actively participate in developing the village potency of the Ancient Volcano Nglanggeran used as ecotourism area. The forms of youth participations such as participation of ideas, participation of efforts, participation of properties, participation of skills and proficiencies, and social participation are given in order to support the developing ecotourism area of Ancient Volcano Nglanggeran. . This study is using observation, in-depth interview, and documentation studies in collecting data. Implementation of the development is not easy, there are several constraints faced by the youth, such as (1) youth participations are not maximized, (2) the limitations of budget and infrastructure, (3) the condition of the environment and natural resource depended on the weather and land degradation, and the prone conditions of earthquakes and landslides, (4) lack of support from various parties. Efforts made by youth in developing ecotourism area of Ancient Volcano Nglanggeran are increasing participation of youth through various support activities, increasing budget and improving infrastructure through cooperation with various parties, conserving natural resources by making ecotourism area, following and winning races to get supports from various parties This developing ecotourism area has implications for the villagers resilience economy, social community, environmental conservation, . infrastructure development, and youth development in the Nglanggeran village. Keywords: Youth Participation, Ecotourism, Villagers Resilience